Design for thermal stresses - Barron, Randall F.; Barron, Brian R. (Hoboken, N.J. : Wiley, 2012)
'This resource presents accessible coverage for designers of equipment that focuses on the basics through advanced design techniques for thermal stresses. Various numerical and analytical design approaches are introduced for thermal stresses, and example problems are included to illustrate the application of the principles for practicing engineers and students. Numerous problems and exercises further reinforce the coverage'--Provided by publisher.
Machine generated contents note: Preface.Nomenclature.Chapter 1. Introduction.1.1 Definition of Thermal Stress.1.2 Thermal-Mechanical Design.1.3 Factor of Safety in Design.1.4 Thermal Expansion Coefficient.1.5 Young's Modulus.1.6 Poisson's Ratio.1.7 Other Elastic Moduli.1.8 Thermal Diffusivity.1.9 Thermal Shock Parameters.1.10 Historical Note.Chapter 2. Thermal Stresses in Bars.2.1 Stress and Strain.2.2 Bar Between Two Supports.2.3 Bars in Parallel.2.4 Bars With Partial Removal of Constraints.2.5 Non-uniform Temperature Distribution.2.6 Historical Note.Chapter 3. Thermal Bending.3.1 Limits on the analysis.3.2 Stress relationships.3.3 Displacement relations.3.4 General thermal bending relations.3.5 Shear bending examples.3.6 Beam bending examples.3.7 Thermal Bowing of Pipes.3.8 Historical Note.4. Thermal Stresses in Trusses and Frames.4.1 Elastic Energy Method.4.2 Unit Load Method.4.3 Trusses With External Constraints.4.4 Trusses With Internal Constraints.4.5 The Finite Element Method.4.6 Elastic Energy in Bending.4.7 Pipe Thermal Expansion Loops.4.8 Pipe Bends.4.9 Elastic Energy in Torsion.4.10 Historical Note.5. Basic Equations of Thermoelasticity.5.1 Introduction.5.2 Strain Relationships.5.3 Stress Relationships.5.4 Stress-Strain Relations.5.5 Temperature Field Equation.5.6 Reduction of the Governing Equations.5.7 Historical Note.Chapter 6. Plane Stress.6.1 Introduction.6.2 Stress Resultants.6.3 Circular Plate With a Hot Spot.6.4 Two-Dimensional Problems.6.5 Plate With a Circular Hole.6.6 Finite Element Solution for Plane Strain Problems.6.7 Historical Note.Chapter 7. Bending Thermal Stresses in Plates.7.1 Introduction.7.2 Governing Equations for Bending of Rectangular Plates.7.3 Boundary Conditions For Plate Bending.7.4 Bending of Simply-Supported Rectangular Plates.7.5 Rectangular Plates With Two-Dimensional Temperature Distributions.7.6 Axisymmetrical Bending of Circular Plates.7.7 Axisymmetric Thermal Bending Examples.7.8 Circular Plates With a Two-Dimensional Temperature Distribution.7.9 Historical Note.Chapter 8. Thermal Stresses in Shells.8.1 Introduction.8.2 Cylindrical Shells with Axisymmetrical Loading.8.3 Cooldown of Ring-Shiffened Cylindrical Vessels.8.4 Cylindrical Vessels with Axial Temperature Variation.8.5 Short Cylinders.8.6 Axisymmetrical Loading of Spherical Shells.8.7 Approximate Analysis of Spherical Shells Under Axisymmetric Loading.8.8 Historical Note.Chapter 9. Thermal Stresses in Thick-Walled Vessels.9.1 Introduction.9.2 Governing Equations for Plane Strain.9.3 Hollow Cylinder with Steady-state Heat Transfer.9.4 Solid Cylinder.9.5 Thick-walled Spherical Vessels.9.6 Solid Spheres.9.7 Historical Note.Chapter 10. Thermoelastic Stability.10.1 Introduction.10.2 Thermal Buckling of Columns.10.3 General Formulation for Beam-Columns.10.4 Post-buckling Behavior of Columns.10.5 Lateral Thermal Buckling of Beams.10.6 Symmetrical Buckling of Circular Plates.10.7 Thermal Buckling of Rectangular Shells.10.8 Thermal Buckling of Cylindrical Shells.10.9 Historical Note.Appendix A. Preferred prefixes in the SI system of units.Appendix B. Properties of material at 300 K.Appendix C. Properties of selected materials as a function of temperature.Appendix D. Bessel Functions.Appendix E. Kelvin Functions.Appendix F. Matrices and determinants.
Includes bibliographical references and index.
Keywords: Thermal stresses